Pengaruh strategi pemasaran terhadap kepuasan konsumen pada jasa persewaan buku kotaro Kota Madiun - Ryan Aikas Priono Arianto (Universitas PGRI Madiun, 2017)
This study aims to determine the marketing strategy to customer satisfaction in the town of Madiun, to determine customer satisfaction in the book rental services Kotaro Madiun, to determine customer satisfaction in the book rental services Kotarodi Madiun. The samples in this study using a random sampling of 100 consumers renting libraries Slovin Kotaro formula obtained 46 samples. Collecting data using the method of documentation and questionnaires. To test the validity of data to test the validity and reliability. The questionnaire that has been deployed processed using IJI correlations and Cronbach alpha, while the hypothesis using simple linear regression and processed using SPSS 1.6. for windows. The results showed that marketing strategies have relationships and a positive effect on customer satisfaction in the book rental services Kotaro Madiun. T test obtained t value of 6.853 with sig 0,000 while ttab at the level of 0.05 at 1.684. It can be said thit > ttab (6.853 > 1.684) or Sighit < Sigprob (0.000 < 0.05) this situation is no different do can influence marketing strategies to customer satisfaction in the book rental services Kotaro Madiun.